The Effect of Omega 3 on Nerve Impulse Speed, Muscular Activity, Cholesterol Level and the Relationship with Performing Some Volleyball Skills - NOORULDEEN ISSA, SAMAH (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in studying the effect of omega 3 on some physiological abilities including speed of nerve impulse, muscular activity and cholesterol level in blood due to their great effect on athletic performance. The study aimed at identifying the effect of omega 3 on nerve impulse speed, muscular activity and cholesterol level in blood and its relationship with the performance of some volleyball skills. The researcher hypothesized a statistical relationship between omega 3, nerve impulse speed and cholesterol level in blood as well as finding a relationship among these variables. The researcher recommended taking omega 3 according to doctor’s order has positive effects.